FEED MANAGEMENT INNOVATIONS FOR ENHANCING THE GROWTH PERFORMANCE OF VANNAMEI SHRIMP LARVAE (LITOPENAEUS VANNAMEI) - Roslina, Roslina; Rizky, Putri Nurhanida; Arifin, Moh. Zainal (Jurnal Perikanan Unram, 2025)
Feed management is a crucial component in the cultivation of vannamei shrimp, particularly during the larval stage which requires complex and varied nutritional needs. This study aims to explore innovative feed management strategies by combining natural and artificial feeds in an industrial-scale setting at Hatchery PT Suri Tani Pemuka, Bali. Natural feeds used included Thalassiosira sp. and Artemia salina, along with six types of artificial feeds administered throughout the larval rearing period from Nauplius to Post Larva (PL) 11 stages. Growth parameters, larval health, and water quality were regularly monitored. The results showed that this feed combination provided high nutritional content (45–60% protein, 16–23% fat) and favorable larval survival rates, ranging from 63.62% to 76.15% across the three rearing tanks. There were no significant differences in larval length among tanks (P>0.05), and water quality parameters remained within optimal thresholds. Microscopic observations supported visual assessments, indicating good physiological development in the larvae. This innovative feeding strategy demonstrates strong potential to enhance the sustainability and efficiency of vannamei shrimp larval aquaculture